Presence of Helicobacter pylori infection in gastroduodenal perforations - T., Kemparaj; Bagur, Ashika (International Surgery Journal, 2020)
Background: Gastroduodenal perforations constitute one of the commonest surgical emergencies encountered. Helicobacter pylori is a gram negative bacterium that has infected more than half the world’s population. The most commonly recognized manifestation of H. pylori infection in India is peptic ulcer disease. Although the relationship between H. pylori infection and peptic ulcer has been well defined, the relationship of H. pylori infection with gastroduodenal perforation is still controversial. The objective of the study was to determine the presence of H. pylori in gastroduodenal perforations. Methods: We conducted a prospective study, noting the number of cases which turned out to be positive for H. pylori in cases of gastroduodenal perforations intraoperatively, using rapid urease test. Results: Out of 100 cases of gastroduodenal perforations operated, 74% were positive for the test. Gastric perforations positive for the test were 81.4% and duodenal perforations positive for the test were 68.42%. Conclusions: There is a positive attribution between H. pylori infection and gastroduodenal perforations.